(untitled) (Bangladesh Veterinarian, 2013)
Fifty beef carcasses were used to determine the effects of High Voltage Electrical Stimulation (HVES, 800 Volts) on pH and meat quality. Meat from M. longissimus dorsi was examined for pH and temperature at 1, 2, 5, 10 and 24 hours, while tenderness and colour were examined seven days after slaughter. HVES decreased the pH of the meat and accelerated rigor mortis (P<0.05). HVES improved tenderness and colour compared with the control group across the ageing period at 4oC. It is suggested that HVES had positive effects on tenderness and colour. DOI: http://dx.doi.org/10.3329/bvet.v30i1.16283 Bangl. vet. 2013. Vol. 30, No. 1, 33-38